Health and Fitness of Buddhists in the Kathmandu Valley - Shahi, Suresh Jung; Shrestha, Madhav Kumar (ILAM इलम, 2023)
This study, entitled "Health and Fitness of Buddhists in the Kathmandu Valley," was carried out to identify the techniques for achieving good health and physical fitness in Buddhists. The necessary information was taken from the eleven monasteries and Bihar in the Kathmandu Valley. The major sources of data were primary and secondary. This study was based on an explanatory research design. Buddhism strongly believes that human characteristics like greed, anger, and ignorance are the three most serious psychological diseases. Buddha also presented his teachings on avoiding all evil, killing and harming living beings, cultivating good and cleansing one's mind. It is very important to achieve good health and physical fitness. Through meditation and walking meditation, the body achieves a greater state of balance, physical conditions improve, fighting against diseases is regulated, and breathing is regulated. Our minds become focused, clear, and organized. Unnecessary desires and improper thoughts are eliminated. Therefore, the researcher has concluded that Buddhist rules and the code of conduct are the best ways to achieve good physical, mental, and spiritual health and fitness.